Credibility assessment : scientific research and applications - Raskin, David C.; Honts, Charles; Kircher, John. (Amsterdam : Academic Press, 2014)
'In 2001, the late Murray Kleiner and an array of experts contributed to the Handbook of Polygraph Testing, published by Elsevier, which examined the fundamental principles behind polygraph tests and reviewed the key tests and methods used at that time. In the intervening thirteen years, the field has moved beyond traditional polygraph testing to include a host of biometrics and behavioral observations. This new book reflects the breadth of methods now used.'--back cover.
Strategic use of evidence during investigative interviews: the state of the science / Maria Hartwig, Par Anders Granhag, Timothy Luke -- Credibility assessment at portals / Charles R. Honts, Maria hartwig -- Validity of polygraph techniques and decision methods / David C. Raskin, John C. Kircher -- Countermeasures and credibility assessment / Charles R. Honts -- Detecting deception using ocular metrics during reading / Douglas J. Hacker, B. Brian Kuhlman, John C. Kircher, Anne E. Cook, Dan J. Woltz -- The neural basis of deception and credibility assessment: a cognitive neuroscience perspective / Ray Johnson -- Theories in deception and lie detection / Aldert Vrij, Giorgio Ganis.
Includes bibliographical references and index.
Keywords: Criminal investigation -- Psychological aspects; Interviewing in law enforcement; Police questioning; Forensic psychology